Studying patterns in the flocculation of sludges from wet gas treatment in metallurgical production - Shestopalov, O.; Briankin, Oleksandr; Tseitlin, Musii; Raiko, Valentina; Hetta, Oksana S. (PC Technology center, 2019)
The influence of a solid phase concentration in the model sludges of wet gas purification, as well as the flocculant consumption, on a change in the solid phase sedimentation rate and the strength of floccules has been examined. This is important because fluctuations in the solid phase concentration in waste water represent an uncontrolled process that significantly affects the kinetics of the solid phase sedimentation and leads to an increase in the flocculant consumption. We have proposed a procedure for determining the sedimentation rate of the flocculated sludge and the strength of floccules following the hydromechanical influence, which takes into consideration the solid phase concentration and the flocculant consumption. The study was carried out on model waste water, synthesized by mixing the dust from dry gas purification at actual production site with water. It has been determined that the solid phase concentration affects the rate of floccule deposition. It has been established that the optimum conditions for aggregate formation within a given model system are observed at the solid phase concentration in the interval 8–12 g/l. Increasing the solid phase concentration above 16 g/l decreases the floccule sedimentation rate disproportionately to the flocculant concentration. It is possible to reduce flocculant consumption and to optimize its dosage by carrying out a cleaning process taking into consideration the specified patterns. It was established that the hydromechanical influence on aggregates exerts the destructive effect, whose degree depends on the solid phase concentration. In particular, increasing the rate of fluid motion leads to greater damage to floccules than increasing the time for a less intense exposure. The way to minimize the destructive effect on floccules could be lowering the suspension transportation speed resulting from a decrease in the installation performance or through the increased cross-section of the channel (a pipeline). An increase in the solid phase concentration of the model system above 16 g/l is accompanied by a significant reduction in the strength of floccules. Therefore, when designing wastewater treatment plants that utilize flocculants, it is necessary to provide optimum conditions for aggregation and to minimize the hydromechanical effects on floccules by lowering the velocity of fluid motion.

Досліджено вплив концентрації твердої фази модельних шламів мокрої очистки газу і витрати флокулянта на зміну швидкості осідання твердої фази і міцність флокул. Це важливо, тому що коливання концентрації твердої фази в стічній воді є неконтрольованим процесом і істотно впливає на кінетику осідання твердої фази і приводить до збільшення витрати флокулянта. Запропонована методика виявлення швидкості седиментації сфлокульованого шламу і міцності флокул після гідромеханічного впливу, що враховує концентрацію твердої фази і витрати флокулянта. Дослідження проводилися на модельній стічній воді, синтезованій шляхом змішення пилу сухої газоочищення реального виробництва з водою. Було встановлено, що концентрація твердої фази впливає на швидкість осадження флокул. Встановлено, що оптимальні умови агрегатоутворення даної модельної системи спостерігаються при концентрації твердої фази в інтервалі 8–12 г/л. Із зростанням концентрації твердої фази понад 16 г/л швидкість осадження флокул знижується непропорційно концентрації флокулянта. Зниження витрати флокулянтів і оптимізація його дозування можливі шляхом проведення процесу очищення з урахуванням вказаних закономірностей. Встановлено, що гідромеханічний вплив на агрегати здійснює руйнуючу дію, ступінь якої залежить від концентрації твердої фази. Зокрема збільшення швидкості руху рідини призводить до більшого руйнування флокул, ніж збільшення часу менш інтенсивного впливу. Способом мінімізації руйнуючої дії на флокули може бути зниження швидкості транспортування суспензії в результаті зменшення продуктивності установки або збільшення перетину каналу (трубопроводу). Із зростанням концентрації твердої фази в модельній системі понад 16 г/л спостерігається істотне зниження міцності флокул. Тому при проектуванні установок очищення стічної води із застосуванням флокулянтів необхідно забезпечити оптимальні умови агрегатоутворення і мінімізувати гігдромеханічні впливи на флокули шляхом зниження швидкості руху рідини.
Дослідження закономірностей флокуляції шламів мокрої газоочистки металургійного виробництва
Keywords: flocculation; aggregation; strength of aggregates; deposition rate; optimization; hydromechanical destruction of floccules; агрегатоутворення; міцність агрегатів; швидкість осадження; гідромеханічне руйнування флокул; оптимізація